Exploring the impact of external focus of attention on vertical jump performance: a systematic review - Mufan Zhang; Jiong Luo; Tingran Zhang (Brazilian Journal of Health Review, 2026)
Objective: To explore the impact of external focus of attention on vertical jump (VJ) performance, synthesizing evidence on how optimizing attentional focus instructions enhances neuromuscular integration and improves VJ outcomes. Method: Following PRISMA guidelines, 12 high-quality experimental studies (totaling 377 participants of varying athletic levels) were selected from databases including PubMed, Web of Science, and the Cochrane Library. Quality was assessed using scales like PEDro, followed by a qualitative descriptive synthesis of performance, biomechanical, and neural control indicators. Results: (1) Compared to internal focus (IF) or neutral instructions, external focus (EF) significantly improved VJ height, peak velocity, and reactive strength index; (2) EF optimized motor unit recruitment, increasing power output while reducing sEMG activity; (3) EF effectiveness depends on goal orientation: spatial goals enhance stretch-shortening cycle (SSC) efficiency, whereas safety-oriented focus optimizes energy absorption but immediately reduces VJ performance; (4) Long-term EF interventions demonstrated superior stability in strength gains, skill retention, and movement pattern remodeling compared to IF. Conclusion: EF enhances VJ performance and neuromuscular efficiency by reducing central monitoring interference and optimizing muscle recruitment. Coaches should tailor EF instructions based on specific training phases (performance enhancement vs. injury prevention) to maximize neural gains.